Eating Habits, Stress Levels, and Food Coping Strategies Associated with the Nutritional Status of Migrant University Students from Kuningan in Jakarta - Anggun Apriani; Chica Riska Ashari (Media Publikasi Cendekia Indonesia, 2026)
Nutritional status reflects the body’s condition and is influenced by daily dietary habits. Adequate and balanced nutrient intake in accordance with body requirements supports good nutritional status. Several factors, including eating habits, stress levels, and food coping strategies, may affect nutritional outcomes. This study aimed to examine the association of these factors with the nutritional status of migrant university students from Kuningan living in Jakarta. A quantitative cross-sectional design was employed. The study involved 72 migrant university students selected through snowball sampling. Data were collected using structured questionnaires and interviews, including the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) to assess eating habits, the Depression Anxiety Stress Scale-21 (DASS-21) to measure stress levels, and the Coping Strategy Index (CSI) to evaluate food coping strategies. Nutritional status was determined using anthropometric measurements of body weight and height to calculate Body Mass Index (BMI). Descriptive analyses were performed to summarize participant characteristics, followed by inferential analysis using the Chi-square test to examine associations between independent variables and nutritional status. Descriptive analysis showed that most students had normal nutritional status, moderate stress levels, and predominantly low food coping strategies. The Chi-square test indicated a significant association between eating habits and undernutrition (p < 0.001), while stress levels (p = 0.317) and food coping strategies (p = 0.704) were not significantly associated with undernutrition. Among migrant university students from Kuningan in Jakarta, eating habits are the primary factor influencing nutritional status. These findings emphasize the need for targeted interventions, such as nutrition education and promotion of balanced meals, to improve dietary behaviors. Universities should support students in adopting healthier eating patterns, especially those living away from home, to maintain optimal nutritional status and enhance academic performance and well-being.